Erectile Dysfunction: Way to Overcome - Roy, Polash (Bangladesh Journal of Medicine, 2024)
Erectile dysfunction (ED) is one of the common condition impacting millions of men worldwide, characterized by the inability to achieve or maintain an erection sufficient for sexual activity. Men suffering ED have multifactorial etiologies, including vascular, neurological, psychological, and hormonal factors. Pharmacological treatments are often the first line of therapy, with phosphodiesterase type 5 inhibitors (PDE5Is) like sildenafil and others showing substantial efficacy and safety. When a individual is unresponsive to oral medications, second-line treatments include vacuum erection devices, intracavernosal injections and intraurethral suppositories. If a person is fail to improve on conventional therapy or intollerable to pharmacological agent or in case of severe cases surgical options, such as penile implants and vascular reconstruction, offer effective solutions. Psychotherapy plays a crucial role, particularly when psychological factors like anxiety, depression, or stress are involved. Cognitive-behavioral therapy (CBT) has shown success in treating psychogenic ED . Additionally, addressing lifestyle factors is imperative; regular exercise, a healthy diet, weight management, smoking cessation, and limited alcohol consumption can significantly enhance erectile function. Pharmacological agent prescribed for other comorbid condition like some antihypertensives, psychotropics etc. may worse the condition of ED and need to evaluate the treatment plan with safer option. Emerging treatments, such as low-intensity shockwave therapy and regenerative medicine (e.g., stem cell therapy and platelet-rich plasma), are gaining traction for their potential to restore erectile function through tissue regeneration and improved vascularization. In conclusion, overcoming ED requires a tailored approach that considers the underlying causes and individual patient needs. Combining pharmacological, psychological, surgical, and lifestyle interventions offers the best outcomes, improving both erectile function and overall quality of life. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 144